Disparities in pay for women and men working in the healthcare sector in Poland in the years 2004-2012 - MACIEJEWSKA, Paula; CZERWIŃSKA, Joanna (Progress in Economic Sciences; No 2 (2015): Progress in Economic SciencesDO - 10.14595/PES/02/010, 2015)
Statistical information provided by Eurostat, the Directorate-General of the European Commission, as well as other national statistical offices show a significant male-female income disparity in Europe. According to Eurostat, the disparity reaches on average 16% in the European Union. Worldwide, the problem has caught the attention of the law makers and activists while in Poland a public debate about the pay gap is only now beginning to g ain in popularity . The Polish Central Statistical Office is the key body that releases the information about the earnings, used here to investigate the problem of sex-based income disparity. Despite the availability of the statistical data however, not much research has been done so far. Herein, we present the statistical analysis regarding the pay gap between male and female doctors, nurses and midwives in Poland. The research employed the regression analysis and the following factors were taken into account: sex, age, work experience, profession and size of the city. Initial hypothesis stated that between 2004 and 2012, sex was the most significant factor de ter mining the male-female health ca re professionals income disparity in Poland.